The Influence Of Human Resource Capabilities And Officer Facilities On The Performance Of Family Planning Counselors - Armaini, Farisa; Kosasih, Kosasih; Utoyo, Widjajanti (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study examines the impact of human resource capability and officer facilities on the performance of Family Planning (KB) counselors in the implementation of the Bangga Kencana Program in Empat Petulai Dangku District in 2024. The research aims to assess how the competencies of KB counselors and the availability of supporting facilities affect program effectiveness. A quantitative approach was used with a sample of 83 respondents, selected via purposive sampling. Data were collected using a Likert scale questionnaire and analyzed through regression analysis. The results show that both human resource capability and the availability of facilities have a significant impact on counselor performance. Well-trained counselors, supported by adequate resources such as educational tools, digital devices, and transportation, are more likely to achieve program objectives. The study emphasizes the need for continuous professional development and resource allocation to optimize the performance of KB counselors. Recommendations for policymakers include enhancing training systems, improving infrastructure, and implementing regular performance evaluations to ensure the success of family planning initiatives.